Herpes Zoster Burden of Disease and Clinical Management in Turkey: A Comprehensive Literature Review - Selim Badur; Esin Senol; Alpay Azap; Cihan Yesiloglu; Alev Ozakay; Serdar Ozturk; Adriana Guzman-Holst (Infectious Diseases and Therapy, 2023)
Abstract Introduction Herpes zoster (HZ), or shingles, is caused by the reactivation of varicella zoster virus (VZV) and typically presents as an acute, painful dermatomal rash, but can lead to long-term, distressing complications such as postherpetic neuralgia (PHN). Increasing trends in HZ cases are evident globally among the aging population; however, reviews investigating the epidemiology and clinical management of HZ in Turkey are lacking. Therefore, a literature review of local studies in Turkey was conducted to identify the data available and identify gaps in the literature. Methods Literature searches were carried out in PubMed and local journals to retrieve published articles that reported surveillance data, seroepidemiology, patient outcomes, or clinical management related to HZ or VZV in Turkey until April 30, 2022. Studies included primary data reports, case studies, secondary data reviews, and epidemiological studies in healthy or at-risk populations; HZ was the primary focus of the review. Results No studies reported VZV or HZ epidemiological data at a national level. One large retrospective study in Istanbul reported that HZ incidence rates significantly increased in adults 18–44 years of age between 2011 and 2019. Four single-center studies reported the proportion of dermatological patients with HZ at 0.43–1.56%. PHN was the most common reported complication, occurring in 8–58.9% of patients with HZ. However, out of 39 identified case reports, HZ ophthalmicus was the most frequently reported complication. Two studies highlighted poor disease awareness and risk perception of HZ among Turkish citizens. Conclusion Overall, there were limited comprehensive epidemiological data on HZ in Turkey. However, the abundance of case studies on HZ complications indicates a strong disease presence and diverse clinical management in Turkey. Further research will be important to understand the impact of HZ, increase disease awareness, and support the introduction of new preventative strategies.